Molecular dynamics study of taxadiene synthase catalysis. Issue 19 (15th February 2018) - Escorcia, Andrés M.; van Rijn, Jeaphianne P. M.; Cheng, Gui‐Juan; Schrepfer, Patrick; Brück, Thomas B.; Thiel, Walter
Abstract : Molecular dynamics (MD) simulations have been performed to study the dynamic behavior of noncovalent enzyme carbocation complexes involved in the cyclization of geranylgeranyl diphosphate to taxadiene catalyzed by taxadiene synthase (TXS). Taxadiene and the observed four side products originate from the deprotonation of carbocation intermediates. The MD simulations of the TXS carbocation complexes provide insights into potential deprotonation mechanisms of such carbocations. The MD results do not support a previous hypothesis that carbocation tumbling is a key factor in the deprotonation of the carbocations by pyrophosphate. Instead water bridges are identified which may allow the formation of side products via multiple proton transfer reactions. A novel reaction path for taxadiene formation is proposed on the basis of the simulations. © 2018 Wiley Periodicals, Inc. Abstract : Taxadiene synthase catalyzes the cyclization reaction of geranylgeranyl diphosphate to five cyclic products, one of which (taxadiene) is a biosynthetic precursor to taxol, a potent anticancer drug. Getting molecular insights into taxadiene synthase catalysis may help to improve the industrial processes currently employed to produce this drug. We present molecular dynamics simulations of enzyme·carbocation intermediates involved in the reaction, which provide information on potential reaction pathways to the observed products.